Epidemie cholery a reformy sanitarne w Wielkiej Brytanii w latach 40. i 50. XIX wieku - Straszak-Chandoha, Sylwia (Epidemics of Cholera and Sanitary Reforms in Great Britain in The 1940s and 1950s of The 19th Century, 2008)
Most governments prepared some rules of health policy to protect people against the epidemic. There have emerged modern sanitation institutions which have been responsible for controlling every-day conditions of people's life: hygiene, standard of living and quality of food.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 186-198